Reimagining Homelessness - O'Sullivan, Eoin (Policy Press, 2020)
Available Open Access under CC-BY-NC licence. The number of people experiencing homelessness is rising in the majority of advanced western economies. Bringing to light the most contemporary research, policy and practice, this book presents stark evidence from Irish experience to argue that we need to urgently reimagine homelessness as a pattern of residential instability and economic precariousness regularly experienced by marginal households.